2017
DOI: 10.3174/ajnr.a5372
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of 70-kV CT Angiography for the Visualization of the Adamkiewicz Artery: Comparison with 120-kV Imaging

Abstract: Seventy-kilovolt CTA has substantial advantages for the identification of the Adamkiewicz artery before aortic repair, with a significantly lower radiation exposure and superior image quality than 120-kV CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Our study indicated that for pediatric patients with weight less than 28 kg, the use of 70kVp tube voltage could reduce about 37% radiation dose and 44% contrast dose while obtaining images that meeting the diagnostic requirement in abdominal CT imaging. Our results are an extension to the results of previous studies for cardiac CT imaging showing that the use of 70kVp could provide images that satisfy the diagnosis requirements with a CM dose reduction of 25%-56% [17][18][19] .…”
Section: Discussionsupporting
confidence: 57%
“…Our study indicated that for pediatric patients with weight less than 28 kg, the use of 70kVp tube voltage could reduce about 37% radiation dose and 44% contrast dose while obtaining images that meeting the diagnostic requirement in abdominal CT imaging. Our results are an extension to the results of previous studies for cardiac CT imaging showing that the use of 70kVp could provide images that satisfy the diagnosis requirements with a CM dose reduction of 25%-56% [17][18][19] .…”
Section: Discussionsupporting
confidence: 57%
“…In recent years, the radiation dose and contrast medium (CM) dose for CTA in children have decreased significantly with the application of low tube voltage and iterative reconstruction (IR) algorithms (11), and the combination of low tube voltage and IR algorithms such as the adaptive statistical iterative reconstruction-V (ASIR-V) is routinely used in our hospital. The latest research has shown that the use of low tube voltage, especially 70 kVp in chest CTA, can significantly improve image contrast (12)(13)(14). Simultaneously, the use of IR algorithms has been shown to reduce image noise (15)(16)(17) effectively, and the combination of these 2 methods can significantly reduce doses and maintain image quality.…”
Section: Introductionmentioning
confidence: 99%
“…Their results seem to be superior to those of our study. However, accurate localisation of the AKA may not have been established because previous studies [8,[13][14][15] did not conduct spinal conventional selective angiography. The most reliable way to visualise the AKA is with conventional selective arterial angiography [16].…”
Section: Discussionmentioning
confidence: 99%